Uniformly coated highly porous graphene/MnO2 foams for flexible asymmetric supercapacitors. (4th April 2018) - Drieschner, Simon; Seckendorff, Maximilian von; Corro, Elena del; Wohlketzetter, Jörg; Blaschke, Benno M; Stutzmann, Martin; Garrido, Jose A
Abstract: Supercapacitors are called to play a prominent role in the newly emerging markets of electric vehicles, flexible displays and sensors, and wearable electronics. In order to compete with current battery technology, supercapacitors have to be designed with highly conductive current collectors exhibiting high surface area per unit volume and uniformly coated with pseudocapacitive materials, which is crucial to boost the energy density while maintaining a high power density. Here, we present a versatile technique to prepare thickness-controlled thin-film micro graphene foams ( μ GFs) with pores in the lower micrometer range grown by chemical vapor deposition which can be used as highly conductive current collectors in flexible supercapacitors. To fabricate the μ GF, we use porous metallic catalytic substrates consisting of nickel/copper alloy synthesized on nickel foil by electrodeposition in an electrolytic solution. Changing the duration of the electrodeposition allows the control of the thickness of the metal foam, and thus of the μ GF, ranging from a few micrometers to the millimeter scale. The resulting μ GF with a thickness and pores in the micrometer regime exhibits high structural quality which leads to a very low intrinsic resistance of the devices. Transferred onto flexible substrates, we demonstrate a uniform coating of the μ GFs with manganese oxide, a pseudocapacitively active material. Considering the porous structure and the thickness of the μ GFs, square wave potential pulses are used to ensure uniform coverage by the oxide material boosting the volumetric and areal capacitance to 14 F cm −3 and 0.16 F cm −2 . The μ GF with a thickness and pores in the micrometer regime in combination with a coating technique tuned to the porosity of the μ GF is of great relevance for the development of supercapacitors based on state-of-the-art graphene foams.